EP 118. Can midday naps boost learning in older adults?. Issue 9 (September 2016) - Backhaus, W.; Braaß, H.; Gerloff, C.; Hummel, F.
Abstract : Background: Naps as well as a night of sleep were found to improve motor learning in young individuals (Doyon et al., 2009 ). The capacity of older adults to learn and stabilize motor memory traces (consolidation) during over-night sleep is limited (Pan and Rickard, 2015; Backhaus et al., 2015 ). However a small number of studies suggested sleep-dependent consolidation in healthy older adults, immediately after sleep (Gudberg et al., 2015; Al-Sharman and Siengsukon, 2014 ) or after a delayed period (Tucker et al., 2011; Korman et al., 2015 ). Research question: Can midday naps enhance motor learning in older adults? Methods: We evaluated the performance changes of a sample of thirty-three healthy older adults (60–82 years) by implementing a napping paradigm in a motor learning setup (sequence learning and motor adaption). The participants were randomly assigned to one of three groups; short nap group (a forty-five minutes nap opportunity, 10–20 min sleep), long nap group (ninety minutes nap opportunity, 50–80 min sleep) or a forty-five minutes period of wakefulness. Three learning sessions on two consecutive days were compared for both tasks with the repeated measures mixed model approach. Results: All older adults were able to improve their task performance in both tasks throughout all sessions. For sequence learning no differences between the nap groups could be found following the midday nap, nor after an extended period of consolidation, i.e. the following day. Similarly no significant differences between the groups could be found directly after the midday break when performing the motor adaptation task. However during the final block of the last session nappers performed significantly better ( p  = 0.023) than those adults staying awake. Conclusion: Although midday naps may have a great recuperative value (Tamaki et al., 1999; Campbell et al., 2011 ), these effects could not be projected on motor learning and subsequent motor performance directly after napping. Based on the current results we conclude that short daytime naps do not enhance the effects of motor learning and consolidation. Thus, deficits in consolidation apparent in older adults are not dependent of the duration of sleep but rather of the process of consolidation during sleep, which seems to be impaired in older adults. This work was supported by the Stiftung der Deutschen Wirtschaft providing a PhD Scholarship to W.B. W.B and F.C.H. hold a research grant from the Werner-Otto-Foundation (9/87).